Nigral Iron Deposition Is Associated With Levodopa-Induced Dyskinesia in Parkinson’s Disease - Song, Tianbin; Li, Jiping; Mei, Shanshan; Jia, Xiaofei; Yang, Hongwei; Ye, Yongquan; Yuan, Jianmin; Zhang, Yuqing; Lu, Jie (Frontiers in Neuroscience, 2021)
Objective :To investigate iron deposition in the substantia nigra(SN) of Parkinson’s Disease(PD) patients associated with Levodopa-induced dyskinesia (LID).Methods:Seventeen PD patients with LID, 17 PD patients without LID, and 16 healthy controls were recruited for this study. The mean QSM values of the whole, left, and right SN were compared among the three groups. A multivariate logistic regression model was constructed to determine the factors associated with an increased risk of LID. The receiver operating characteristic curve of the QSM value of SN in discriminating PD with and without LID was evaluated.Results:The mean QSM values of the whole and right SN in the PD with LID was higher than that of PD without LID (*P = 0.03, *P = 0.03). Multivariate logistic regression analysis revealed that the QSM value of whole, left or right SN was a predictor of the development of LID(*P = 0.03, *P = 0.04 and *P = 0.04). The predictive accuracy of LID in adding the QSM value of the whole, left and right SN to LID-related clinical risk factors were 70.6%, 64.7% and 67.6% respectively. The QSM cutoff values between PD with and without LID of the whole, left and right SN were 148.3 ppb, 165.4 ppb and 152.7 ppb respectively. Conclusion: This study provides the evidence of higher iron deposition in the SN of PD patients with LID than those without LID, suggesting that the QSM value of the SN may be a potential early diagnostic neuroimaging biomarker for LID.